Regulation of Synaptosomal GLT-1 and GLAST during Epileptogenesis. (15th July 2019) - Peterson, Allison R.; Binder, Devin K.
Abstract: Astrocytes regulate extracellular glutamate homeostasis in the central nervous system through the Na + -dependent glutamate transporters glutamate transporter-1 (GLT-1) and glutamate aspartate transporter (GLAST). Impaired astrocyte glutamate uptake could contribute to the development of epilepsy but the regulation of glutamate transporters in epilepsy is not well understood. In this study, we investigate the expression of GLT-1 and GLAST in the mouse intrahippocampal kainic acid (IHKA) model of temporal lobe epilepsy (TLE). We used immunohistochemistry, synaptosomal fractionation and Western blot analysis at 1, 3, 7 and 30 days post-IHKA induced status epilepticus (SE) to examine changes in GLT-1 and GLAST immunoreactivity and synaptosomal expression during the development of epilepsy. We found a significant upregulation in GLT-1 immunoreactivity at 1 and 3 days post-IHKA in the ipsilateral dorsal hippocampus. However, GLT-1 immunoreactivity and synaptosomal protein levels were significantly downregulated at 7 days post-IHKA in the ipsilateral hippocampus, a time point corresponding to the onset of spontaneous seizures in this model. GLAST immunoreactivity was increased in specific layers at 1 and 3 days post-IHKA in the ipsilateral hippocampus. GLAST synaptosomal protein levels were significantly elevated at 30 days compared to 7 days post-IHKA in the ipsilateral hippocampus. Our findings suggest that astrocytic glutamate transporter dysregulation could contribute to the development of epilepsy. Highlights: GLT-1 synaptosomal protein levels are downregulated during epileptogenesis. Insufficient astrocyte glutamate uptake may contribute to epileptogenesis. GLAST synaptosomal protein levels are elevated at chronic time points.